Design and Analysis of Power Transmission Monopole Using ETABS - Subramani, T; Prakash, B (International Journal of Engineering and Technology, 2018)
Electricity consumption is day by day increase for each and every application. Transmitting the power source from production place to designation place via steel wire is followed by ancient people. In this we use heavy towers which carry minimum of 2000kw power in each line which is hanged in the towers. These towers are subjected to dynamic and static load cases. Hence in this thesis we proposed to design and analysis the power transmission towers in our places. We introduce type of tower and its configuring ratio as per Indian standard IS-802. A standard kind of transmission line tower selected as case examine is analyzed and modeled the usage of ETABSs software. Loads acting on the tower are wind load, dead load of the structure, braking load of conductor and earthquake load considered as per Indian standard. The place of tower underneath seismic and wind is region III. The wind pressure depends on the gust response component which will increase with height. Seismic and wind analysis is finished the usage of standard codes using ETABSs software program. The conduct of tower is analyzed for distinctive load mixtures. The most displacement values, shear forces and bending moments are obtained and are plotted graphically. Â Â Â